Short-term oral atrazine exposure alters the plasma metabolome of male C57BL/6 mice and disrupts α -linolenate, tryptophan, tyrosine and other major metabolic pathways - Lin, Zhoumeng; Roede, James R.; He, Chunla; Jones, Dean P.; Filipov, Nikolay M. (My University, 2015)
Overexposure to the commonly used herbicide atrazine (ATR) affects several organ systems, including the brain. Previously, we demonstrated that short-term oral ATR exposure causes behavioral deficits and dopaminergic and serotonergic dysfunction in the brains of mice. Using adult male C57BL/6 mice, the present study aimed to investigate effects of a 10-day oral ATR exposure (0, 5, 25, 125, or 250 mg/kg) on the mouse plasma metabolome and to determine metabolic pathways affected by ATR that may be reflective of ATR’s effects on the brain and useful to identify peripheral biomarkers of neurotoxicity. Four h after the last dosing on day 10, plasma was collected and analyzed with high-performance, dual chromatography-Fourier-transform mass spectrometry that was followed by biostatistical and bioinformatic analyses. ATR exposure (≥5 mg/kg) significantly altered plasma metabolite profile and resulted in a dose-dependent increase in the number of metabolites with ion intensities significantly different from the control group. Pathway analyses revealed that ATR exposure strongly correlated with and disrupted multiple metabolic pathways. Tyrosine, tryptophan, linoleic acid and α-linolenic acid metabolic pathways were among the affected pathways, with α-linolenic acid metabolism being affected to the greatest extent. Observed effects of ATR on plasma tyrosine and tryptophan metabolism may be reflective of the previously reported perturbations of brain dopamine and serotonin homeostasis, respectively. ATR-caused alterations in the plasma profile of α-linolenic acid metabolism are a potential novel and sensitive plasma biomarker of ATR effect and plasma metabolomics could be used to better assess the risks, including to the brain, associated with ATR overexposure.
Keywords: Atrazine; Metabolomics; Biomarker; Pesticide; Metabolic pathway analysis; Dual chromatography-Fourier-transform mass spectrometry (DC-FTMS)